Prevalence and structure of dentoalveolar anomalies among adolescents - Drock, V. (Actual Dentistry, 2018)
Relevance of the topic. Dentofacial anomalies are the main dental diseases, and are characterized by high prevalence. According to modern authors, abnormalities and deformations of the dentoalveolar system in children and adolescents contribute to the deterioration of dental health in the future, causing medical, social and economic damage. The aim of the study was to study the prevalence and structure of dentoalveolar anomalies in adolescents. Material and methods of investigation. A total of 1920 teenagers aged 16 to 17 years were examined. The clinical study was carried out according to the standard standard protocol, in accordance with the international statistical classification of diseases and health problems , as well as the classification of Angle’s dentoalveolar anomalies. Results and discussion. The study made it possible to establish that the prevalence of dentoalveolar anomalies in adolescents aged 16–17 is 64.32 ± 1.09% – 1235 people. The most common anomaly of the maxillofacial system is dentoalveolar anomalies, which belong to the first class according to Engle – 506 people, which in a percentage ratio is 26.35±1.01 %. In the second place the distal bite, which corresponds to the 2nd class according to Engle. Its prevalence is 18.23±0.88 %, it was detected in 350 patients examined. The next in frequency there was a deep occlusion in 189 patients, which was 9.84±0.68 %. A shortened bridle of the upper lip was found in 153 adolescents (7.97±0.02 %). A shortened frenum of the tongue was detected in 212 adolescents (11.04±0.72 %). A small vestibule of the oral cavity was observed in 172 examined, which was 8.96±0.65 %. Conclusions. 1. The prevalence of dentoalveolar anomalies in adolescents aged 16-17 is 64.32±1.09 %. 2. The most common anomalies of the dentoalveolar system in adolescents – dentoalveolar anomalies, belonging to the I class according to Engle – 26.35±1.01, %. In the second place the distal bite, which corresponds to the II class according to Engle. Its prevalence is 18.23±0.88 %. A deep bite was detected in 9.84±0.68 % of the examined. 3. Among soft tissue pathologies of the oral cavity, a shorter bridle of the tongue was detected in 11.04±0.72 % of the examined, small girdle of the oral cavity in the second place in prevalence – in 8.96±0.65 %, shortened bridle of the upper lip in 7.97±0.02% of the examined adolescents. Key words: dentoalveolar anomalies, soft tissue anomalies, adolescents.